Blocking CD47 Shows Superior Anti-tumor Therapeutic Effects of Bevacizumab in Gastric Cancer - Chenyang Shi; Jiaxin Li; Guorong Fan; Yu Liu (Frontiers Media S.A., 2022)
Background: Bevacizumab (Avastin®), a humanized antiangiogenic monoclonal antibody, is widely used in the clinical treatment of tumour diseases. However, recent research has shown that the beneficial antiangiogenic effects of these agents have been limited in a number of patients due to complex immunosuppressive mechanisms. Here, we report a synergistic antitumour strategy through simultaneous blockade of VEGF and CD47 signalling to enhance the curative effect of advanced gastric cancer.Method: A BGC-823 gastric tumour model was chosen to evaluate antitumour efficacy. Macrophage migration and phagocytosis were evaluated to determine immune-related resistance to bevacizumab therapy. Synergistic antitumour activity was observed on the basis of tumour volume, tumour weight, tumour inhibition rate, tumour angiogenesis and tumour metastasis when bevacizumab was combined with an anti-CD47 monoclonal antibody.Results: Our study demonstrated that synergistic therapy targeting CD47 and VEGF reversed macrophage migration and phagocytosis, which were inhibited by antiangiogenic therapy and enhanced antitumour effects. Moreover, blockade of CD47 induced by antiangiogenic therapy inhibited tumour metastasis.Conclusion: Our data provide an effective strategy to attenuate resistance to bevacizumab therapy, promoting clinical cancer treatment with antiangiogenic drugs in combination with CD47-targeting inhibitors.